Peau d’Âne : de la répulsion à la séduction. Parcours de femmes au Maghreb - CHARNAY, Bochra (Ondina - Ondine, 2019)
The Maghrebi versions of Donkey Skin, Arab and Berber, have many features in comparison with the West corpus. The type tale is characterized by a complex structure where sequences are sequenced drawn in Snow-White, The Maiden Without Hands, The Bride Substitued or again The Animal-fiance. The motifs, of great diversity also contribute to this wealth. As an indication, the incestuous brother, the skin of the slave and a male protagonist performing the same course as the Female Donkey Skin. This "Male Donkey Skin" also passes from repulsion to seduction after many tests. The explored corpus puts into question the motives of incest and animal skin as identities of the tale. He enriches them with other discursive elements drawn from the reference culture. Key words: Donkey skin, incest, Maghreb, woman, initiation, ritual, repulsion